DAIRY PRODUCTIVITY OF THE KAZAKH HORSE MARES AND THEIR CROSS BREEDS WITH ROADSTERS - K. Zh. Iskhan; A. R. Akimbekov; A. D. Baimukanov; Kh. A. Aubakirov; A. K. Karynbayev; T. S. Rzabayev; Mukhatai Geminguli; R. Z. Dzhunusova; K. B. Apeev (Scientific Journal of Pedagogy and Economics, 2019)
It has been established that the riding-Kazakh cross breeds in live weight (403-410 kg) outperform the local Kazakh horses (395 kg). In height at withers, the English-Kazakh hybrids (148.5±0.7 cm) are greater than the Arab-Kazakh hybrids (141.2 ± 0.5 cm) and local Kazakh (142.7±0.8 cm). In the chest girth, Arab-Kazakh hybrids (175.8±0.8 cm), on the contrary, exceed the Anglo-Kazakh hybrids (171.7±1.1 cm) and local Kazakh (171.1±1.2 cm). The wide-body index for the English-Kazakh hybrids is 115.62, for the local Kazakh horses - 119.90, for the Arab-Kazakh hybrids - 124.50. It was established that in riding-Kazakh crossbred mares the daily milk yield for 2-4 months of lactation is 7-10 liters. When transiting mares to 4-5-fold milking from the 2nd month of lactation, foals receive less than 2/3 of their mother's milk or 4-6 liters per day. To replenish this under-received amount of milk and to ensure the increase in live weight, the foals ration is additionally included with concentrated feed, hay and green mass.Habituation of colts to feed started from 1.5 months of age. When they are 2 months of age, young animals already consume feed very good. During the suckling period, the live weight of foals from dairy mares in the first 6 months increased by 3.96 times, and from non-milking mares - by 4.22 times. The decrease in the level of milk nutrition in young stock leads to a decrease in the average daily gain. It was found that, on average, during the lactation, the density of milk at production from local Kazakh mares was 1.033°A, while the Arab-Kazakh and English-Kazakh had milk density of 1.032°A. The fluctuations in the fat of the mares of the Kazakh breed for six months of lactation were in the range of 1.1-1.9%, while of the Arab-Kazakh and English-Kazakh hybrids, respectively, 1.3-2.0% and 1.4-2.2 %. That is, the bloodiness of horses does not have a significant impact on the indicators of the chemical composition of the mares' milk.